PENINGKATAN PEMBELAJARAN MENULIS TEKS EKSPOSISI DENGAN MENGGUNAKAN METODE MIND MAPPING PADA SISWA SMA - Budiarti, Sintia; Oktaviana, Syinta; Ahmadi, Yusep (IKIP Siliwangi, 2019)
This research is motivated by the difficulties faced by students when writing exposition texts, one of which is the lack of students' knowledge and interest in writing exposition text because students still feel lazy to express ideas in writing, especially determining their linguistic elements. The statement is based on the results of interviews with Indonesian language subject teachers. So that researchers try to improve the creativity of students in writing exposition texts, one of them is by using the mind mapping method in learning to write exposition text. The researcher used an experimental method with design (one group pre-post test) by collecting data in the form of final test results (pre-test) and final test (post-test) with a sample of 25 high school students. Based on the research data, the comparison of the results of exposition text writing learning with mind mapping method influences the learning process can be proven from the results of the comparison obtained by students having quite significant comparisons, before using mind mapping methods obtain an average value of 74.96 and after using the method have average value of 83.16. So learning using the mind mapping method can be applied in learning exposition text writing because there is an increase in the results of the average student score.